Systematic review of the CUP trials characteristics and perspectives for next-generation studies. (June 2022) - Rassy, Elie; Labaki, Chris; Chebel, Roy; Boussios, Stergios; Smith-Gagen, Julie; Greco, F. Anthony; Pavlidis, Nicholas
Highlights: Over the last five years, CUP research involved primarily retrospective studies. Prospective studies and clinical trials constituted a small proportion of CUP research. The main topics were diagnostics (genomics) and treatment (empiric therapy). Ongoing trials focus on multiple tumour types and are primarily phase II single-arm trials. Two clinical trial designs are suggested to improve the quality of CUP research. Abstract: Background: Research on therapeutic strategies for patients with unknown primary cancer (CUP) has been underwhelming. This paper summarized and evaluated the CUP therapeutic research over the previous five years. Based on this evaluation, recommendations for clinical trial designs are made to improve the impact of CUP research on patients. Methods: Published and ongoing research were evaluated. PubMed was searched from January 1, 2015, to November 1, 2021. The start date of 2015 was chosen to identify research published after ESMO issued new diagnostic and therapeutic guidelines. The US National Library of Medicine indexed ongoing clinical trials. Findings: Of the 244 CUP studies indexed in PubMed, 11.9% were prospective studies, and 4.9% were clinical trials. The review protocol deemed 65 publications eligible for full-text review. Eleven studies evaluating therapeutic regimens were retained. The two prospective studies and non-randomized trials showed promising outcomes for site-specific treatments. Randomized clinical trials were less promising; however, the trials had recruitment challenges resulting in biased accrual and the inability to keep pace with advancing diagnostics and therapeutics. Most of the 35 ongoing studies were phase II single-arm trials assessing immune checkpoint inhibitors (ICI) or site-specific therapies among CUP patients with suspected favorable prognoses. Conclusion: Our evaluation suggests two prospective clinical trial designs that addressed recent study design and recruitment challenges. A visionary approach uses a multi-arm, multistage randomized trial to address rapid advancements in diagnosis and therapy. A pragmatic approach utilizes a single-arm trial with historical controls to overcome comparison group and recruitment challenges.